Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kelurahan Kembangan Selatan Jakarta Barat - Abizar, Mochamad Kemal; Wianti, Wiwin (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The problems in this study focus on achieving optimal employee performance, where performance is not only determined by workload, but also by work environment conditions. An unbalanced workload and a less conducive work environment can reduce employee work effectiveness, so a strategy is needed that is able to create balance and comfort at work. This study aims to determine the influence of workload and work environment on employee performance in South Kembangan Village, West Jakarta. The research method used is quantitative with a statistical approach. The research population amounted to 39 employees with a saturated sampling technique, which involved the entire population as a sample. The analysis technique used was multiple linear regression with the help of SPSS version 27 application. The results showed that workload had a positive and significant effect partially on employee performance by 41%, while the work environment had a positive and significant effect partially by 29.8%. Simultaneously, workload and work environment had a positive and significant effect on employee performance by 70.8%, while 29.2% were influenced by other variables outside the study. Therefore, this study can be concluded that the balance of workload and a conducive work environment contribute greatly to improving employee performance